CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) METHOD IN UZBEKISTAN: CURRENT STATUS, CHALLENGES, AND FUTURE PERSPECTIVES - Rajabova Sevinch Abdulla qizi; Anarkulova Zubayda Fayzullo qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article explores the integration of Content and Language Integrated Learning (CLIL) in Uzbekistan’s educational system. CLIL, a method that combines subject content learning with foreign language acquisition, offers a promising approach to improving both language proficiency and subject knowledge. In many countries, this method has already been successfully implemented to enhance bilingual education. However, Uzbekistan is still in the early stages of its adoption, with several challenges hindering its widespread implementation. This article identifies the obstacles preventing the integration of CLIL into Uzbek schools and discusses potential strategies to overcome them. It also highlights the importance of such integration for Uzbekistan’s educational reforms, aiming to foster a generation of students who are proficient in both their native and foreign languages, thus preparing them for global citizenship.